Investigating the Chronology of Meniscus Root Tears: Do Medial Meniscus Posterior Root Tears Cause Extrusion or the Other Way Around?. Issue 7 (30th July 2021) - LaPrade, Matthew; Hevesi, Mario; Wilbur, Ryan; Song, Bryant; Rhodes, Nicholas; Johnson, Adam; Camp, Christopher; Stuart, Michael; Krych, Aaron
Objectives: Meniscus root tears are increasingly being recognized. Meniscus extrusion has previously been associated with medial root tears; however, the relationship between secondary meniscus restraints, such as the meniscotibial (MT) ligament, extrusion, and root tears has yet to be formally evaluated. The purpose of this study was to better understand the association between MT ligament competence, medial meniscus extrusion, and medial meniscus posterior root tears (MMPRT), as well as to determine the progression of meniscus extrusion over time. Methods: Serial MRI's from our institution were reviewed for patients who showed evidence of medial meniscus extrusion and MMPRT on at least one of 2+ available MRI's. All patients were symptomatic at the time of diagnosis. All MRI's were analyzed independently by two board-certified musculoskeletal radiologists. MT ligament disruption, medial meniscus extrusion, and MMPRT presence was recorded for each MRI. The time between MRI's, presence of insufficiency fractures, and Outerbridge classification for the medial femur and tibia were also evaluated. Results: 27 knees in 26 patients were included in this study, with a total of 63 MRI's analyzed (21 knees with 2 MRI's, 3 with 3 MRI's, and 3 with 4 MRI's). All patients demonstrated clear medial meniscus extrusion and meniscotibial ligament disruption prior to the subsequent development of MMPRTs (p < 0.001). Mean extrusion at the time of initial MRI was 3.3 ± 1.1 mm, and increased significantly to 5.5 ± 1.8 mm at the time of first imaging with an identified MMPRT (p < 0.001). The average time between initial MRI and the first identification of MMPRT on a later MRI was 1.7 ± 1.6 years. Conclusions: In a sample of 27 symptomatic knees with serial MRI's both before and after MMPRT diagnosis, all patients demonstrated MT ligament disruption and associated meniscus extrusion prior to the development of subsequent medial meniscus root tears. These findings suggest that MT ligament disruption and medial meniscus extrusion represent early and predisposing events contributing to MMPRT. Therefore, this provides a possible explanation of why meniscus extrusion is not corrected with medial meniscus root repair.